Dinamika Muhammadiyah Di Kabupaten Musi Banyuasin Provinsi Sumatera Selatan - M Desta Ramadoni; Nor Huda; Sri Suriana (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
Muhammadiyah is an influential organization, especially in reforming the education sector and eradicating all forms of religious practice deviations. The development of Muhammadiyah in the Sumatra region began in 1925 in Minangkabau. Furthermore Muhammadiyah began to rapidly spread to the interior, which was oriented towards the countryside. With the rapid spread of Muhammadiyah to reach the Musi banyuasin Regency, Muhammadiyah established an elementary school in the rural area of ​​Sekayu (Ulak Paceh) in 1926 which is the oldest Muhammadiyah school in the South Sumatra region. Muhammadiyah then began to show its role by carrying out movements in the fields of economy, preaching and social welfare, politics and education